No Straight Answer: Homophobia as Both an Aggravating and Mitigating Factor in New Zealand Homicide Cases - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2006)
This article discusses recent New Zealand homicide cases in which male defendants have sought to rely on the partial defence of provocation to excuse the killing of a man who allegedly made them the subject of unwanted sexual advances. The author argues that at least in cases in which such claims are unsuccessful, reference should be made to section 9(1)(h) of the Sentencing Act 2002, which renders homophobia an aggravating feature in sentencing. To the extent that section 9(1)(h) is not relied on, while provocation is successfully pleaded in some cases, the author concludes that gay male citizens are not afforded equal protection under the criminal law.